HABIBIE PADA SIDANG UMUM MPR RI TAHUN 1999: MASALAH DI TIMUR SELESAI DI JAKARTA - Fahmi Fahmi (Historiography: Journal of Indonesian History and Education, 2021)
Being a leader who reaps a lot of controversy, Habibie is able to deal with it. Resolving domestic issues is his responsibility. The East Timuor issue is a severe case which he faces to its conclusion. Even so, the ending of the East Timor case made Habibie rejected at the time of the accountability trial. Habibie is considered to have neglected his responsibility in defending the KNRI. Menjadi pemimpin yang menuai banyak kontroversi, Habibie mampu menghadapinya. Menyelesaikan persoalan dalam negeri sudah menjadi tanggung jawabnya. Persoalan Timuor Timur merupakan kasus yang berat yang dihadapinya hingga tuntas. Meskipun demikian, berakhirnya kasus Timor Timur itulah membuat Habibie ditolak pada saat sidang pertanggung jawaban. Habibie dianggap sudah lalai dari tanggung Jawabnya dalam mempertahankan KNRI.